The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s1516-35982009001000010
|View full text |Cite
|
Sign up to set email alerts
|

Study of methodological variations in apparent nutrient metabolism determination in broiler chickens

Abstract: -An experiment was conducted to define a protocol to determine metabolizable nutrient and energy values of diets. The metabolizability (M) was calculated of the dry matter (DM); crude protein (CP); gross energy (GE) and AME n of a single diet. Eighty-one 21-day old (d) male birds were used. The tested methodologies were: Cr 2 O 3 (0.5%) as an indicator (partial collection) or Fe 2 O 3 (1%) as a marker; fasting (0, 4, 6 and 8 h) prior to excreta collection and at the end of the feeding period on the last day of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The transit time obtained in the present study was higher than that found by Cortés et al (2009), d, using the same methodoogy and, found an average transit time of 228 minutes in 21-d-old broilers. SG birds presented higher DTT as compared to FGAL at 19 days of age (p < 0.001).…”
Section: Effect Of Dietary Fiber Genetic Strain and Age On The Digescontrasting
confidence: 69%
“…The transit time obtained in the present study was higher than that found by Cortés et al (2009), d, using the same methodoogy and, found an average transit time of 228 minutes in 21-d-old broilers. SG birds presented higher DTT as compared to FGAL at 19 days of age (p < 0.001).…”
Section: Effect Of Dietary Fiber Genetic Strain and Age On The Digescontrasting
confidence: 69%
“…In this regard, Zanella et al (1999) explained that the low recovery rate of chromium oxide led to lower ME values than those obtained by total collection in a study with broilers. Although chromium oxide is largely utilized, Cortés et al (2009) assumed that there might be variability among results due to the difficulty in reproducing them in some laboratories and the incomplete recovery of this marker from the feces, resulting in underestimated concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The total collection method was used to determine metabolism. An initial adaptation period of four days was observed for the birds to adapt to the diet and environment, after which period total excreta collection was performed for three days (Cortés et al, 2009). The excreta were collected in plastic bags twice each day (09.00 and 16.00 h) to prevent fermentation and stored at -10 °C until further analysis.…”
Section: Methodsmentioning
confidence: 99%